Definition and standardization of method for comparative Cone Beam Computed Tomography (CBCT) examination of maxillofacial bone surgery - Roland Decker; Zoltán Fábián; Iván Decker; Sándor Bogdán; László Restár; András Dúcz; Zsolt Németh; Tamás Huszár (Hungarian Dental Association, 2021)
Exact evaluation of the effectiveness of bone replacement surgery in the maxillofacial region has not been established yet. This is due to the difficulty of comparing images performed at different times. There are softwares suitable for comparative testing, but their application is difficult. A standardized comparison procedure for the maxillofacial region has not been developed yet. Objective: 1) To develop and test a method for comparative CBCT analysis of bone replacement surgery in the maxillofacial region. 2) Preparation of a methodological recommendation. Material and Method: CBCT images of 6 patients performed at two different times were compared with HorosTM medical imaging program based on the detection of misalignment. The study was performed by 4 independent investigators. Study groups: 1) Measurements based on standard anatomical points, 2) Measurements based on individual radiological points. Statistics: 3 measurements in every group, Mann-Whitney U test, (SD p ≤ 0,05) Results: The rate of misalignment was significantly lower in case of every measurement based on individual radiolog points than in case of measurements based on anatomical points (1st investigator: 0,463 ± 0,103 vs. 0,283 ± 0,030; 2nd investigator: 0,499 ± 0,100 vs. 0,318 ± 0,040; 3rd investigator: 0,647 ± 0,555 vs. 0,291 ± 0,388; 4th investigator: 0,607 ± 0,069 vs. 0,281 ± 0,033) Conclusions: With the HorosTM imaging software, it is possible to perform an objective comparative study of CBCT images preformed at different time of the same person using the "fitting error measurement" method. The most accurate measurements are achieved by the triangular designation of individual radiologoc points.